Analysis Students Psychosocial Problems During Distance Learning And Importance Role of Teacher's to Overcome - Novita Sari Tanuwijaya; Mesta Limbong (Universitas Pahlawan Tuanku Tambusai, 2022)
For more than two years corona pandemic has occured in our country and has caused learning process changed. Offline school activities can only be done in limited basis and even in some schools cannot be held and still have to do full online. Many problems have happened to students during distance learning that involved students psychosocial. This paper will research psychosocial threats that has occured to students during a pandemic and the important role of teachers in overcoming these threats. The research method used is qualitative research by analyzing and collaborative survey results from trusted organization and comission. From the the data reaserached obtained, it can be seen that there were some student psychosocial problems in distance learning, so that the role of the teacher in managing appropriate learning is very important where the teacher must be able to act as a designer that compile what content is taught, identify the student profile and to map the student's condition, as well as providing motivation and building communication with students. The teacher must in charges in the learning method implementation as a facilitator and provides digital literacy to students to counteract the negative impacts that can arise from prolonged use of gadgets